Early psychological responses of children and caregivers in the immediate aftermath of release from war captivity - Maya Fennig; Avigal Snir; Avigal Snir; Maayan Shorer; Maayan Shorer; Efrat Bron Harlev; Efrat Bron Harlev; Efrat Bron Harlev; Silvana Fennig; Silvana Fennig; Silvana Fennig (Frontiers in Psychology)
BackgroundCaptivity—particularly the captivity of children—is one of the most extreme violations of civilian rights in armed conflict. Despite this, most research on war captivity has focused on adult soldiers, leaving largely unexplored the unique psychological reactions of children subjected to such trauma.ObjectiveThis study aims to (1) describe children and caregivers' early psychological responses immediately following their release from captivity in the Israeli-Hamas war and (2) examine the clinical interventions used to manage these reactions.MethodsThis qualitative study analyzed the psychological reactions of children and their caregivers (N = 26) who were released from captivity and received care at Schneider Children's Medical Centre of Israel. Data collection methods included a review of medical files and in-depth interviews with practitioners (n = 37), including social workers, psychologists, psychiatrists, nurses, and pediatricians, who provided health- and psychosocial care.ResultsPsychological responses were influenced by developmental stage and captivity context. Among young children (2–11 years), predominant reactions included excessive worry, repetitive questioning, traumatic reenactment (e.g., through play), separation anxiety, hypervigilance, anger outbursts, low frustration tolerance, and sleep disturbances. Adolescents (12–18 years) primarily exhibited avoidance, hyperarousal, sleep disturbances, and excessive sharing of traumatic experiences. Caregivers (19–80 years) displayed reactions similar to those of adolescents but also demonstrated dissociative reactions. Interventions were based on the principles of the Psychological First Aid (PFA) model and tailored to the specific reactions of children and caregivers.Conclusions: This study is the first to provide qualitative data on the psychological responses of children and caregivers following war captivity. The findings highlight the need for a family-oriented approach to mental health interventions, particularly for supporting young children and their caregivers. Training practitioners to recognize developmentally specific reactions in the immediate aftermath of captivity is critical for effective assessment, care, and psychopathology prevention. The study concludes with recommendations for improving practice and policy to address this severe and complex violation of children's rights.